Comparison of women and men in biomedical informatics scientific dissemination: retrospective observational case study of the AMIA Annual Symposium: 2017–2020. (28th June 2021) - Hartzler, Andrea L; Leroy, Gondy; Daurelle, Brenda; Ochoa, Magali; Williamson, Jeffrey; Cohen, Dasha; Stipelman, Carole
Abstract: Objective: Although the representation of women in science has improved, women remain underrepresented in scientific publications. This study compares women and men in scholarly dissemination through the AMIA Annual Symposium. Materials and Methods: Through a retrospective observational study, we analyzed 2017–2020 AMIA submissions for differences in panels, papers, podium abstracts, posters, workshops, and awards for men compared with women. We assigned a label of woman or man to authors and reviewers using Genderize.io, and then compared submission and acceptance rates, performed regression analyses to evaluate the impact of the assumed gender, and performed sentiment analysis of reviewer comments. Results: Of the 4687 submissions for which Genderize.io could predict man or woman based on first name, 40% were led by women and 60% were led by men. The acceptance rate was smilar. Although submission and acceptance rates for women increased over the 4 years, women-led podium abstracts, panels, and workshops were underrepresented. Men reviewers increased the odds of rejection. Men provided longer reviews and lower reviewer scores, but women provided reviews that had more positive words. Discussion: Overall, our findings reflect significant gains for women in the 4 years of conference data analyzed. However, there remain opportunities to improve representation of women in workshop submissions, panel and podium abstract speakers, and balanced peer reviews. Future analyses could be strengthened by collecting gender directly from authors, including diverse genders such as non-binary. Conclusion: We found little evidence of major bias against women in submission, acceptance, and awards associated with the AMIA Annual Symposium from 2017 to 2020. Our study is unique because of the analysis of both authors and reviewers. The encouraging findings raise awareness of progress and remaining opportunities in biomedical informatics scientific dissemination.